2019
DOI: 10.1002/bmb.21307
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Three‐Dimensional Virtual Reality Biology Lab versus Conventional Didactic Practices in Lab Experimenting with the Photonic Microscope

Abstract: This study presents the integration of three different teaching scenarios, during biology laboratory lessons, with the overall aim of exploring the potential predominant effectiveness of teaching and improvement of students' learning, by the use of the three‐dimensional virtual reality educational tool Onlabs, versus more traditional didactic practices. A sample of 83, fourth year, undergraduate students of the Primary Education Department of Patras' University in Greece, were equally separated into three cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 17 publications
0
20
0
4
Order By: Relevance
“…Since the initial introductions of the VL concepts, research on the effectiveness of VLs confirmed that properly designed virtual simulation tools can enhance students' learning processes [9], [10]. As a result, VLs have been implemented and/or studied across the wide variety of disciplines, such as life science (e.g., biology) [11], [12], [13], [14], [15], physical sciences (e.g., physics and chemistry) [16], [17], [18], [19], [20], mathematics/computer sciences [21], [22], [23], [24], [25], and engineering [26], [27], [28], [29], [30]. However, we will need to be careful when using the term "virtual lab" since there is no set definition for "virtual lab."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the initial introductions of the VL concepts, research on the effectiveness of VLs confirmed that properly designed virtual simulation tools can enhance students' learning processes [9], [10]. As a result, VLs have been implemented and/or studied across the wide variety of disciplines, such as life science (e.g., biology) [11], [12], [13], [14], [15], physical sciences (e.g., physics and chemistry) [16], [17], [18], [19], [20], mathematics/computer sciences [21], [22], [23], [24], [25], and engineering [26], [27], [28], [29], [30]. However, we will need to be careful when using the term "virtual lab" since there is no set definition for "virtual lab."…”
Section: Literature Reviewmentioning
confidence: 99%
“…There can be no question as to the potential of VR for training in various situations, including laboratory protocols. 17,18 Research using platforms such as Labster and Onlabs suggests that VR training environments can be useful complements to traditional lab classes. VR is already being used in many molecular research contexts including drug discovery 19 and omic data sets.…”
Section: Role Of Virtual Reality?mentioning
confidence: 99%
“…It is emotive, it is immersive and engaging, it is collaborative, and it works across distance and presents novel opportunities to work in ways that represent how to learn rather than what to learn. There can be no question as to the potential of VR for training in various situations, including laboratory protocols 17,18 . Research using platforms such as Labster and Onlabs suggests that VR training environments can be useful complements to traditional lab classes.…”
Section: Role Of Virtual Reality?mentioning
confidence: 99%
“…Virtual laboratories have overall positive effects on students’ cognitive load, skills development and motivation [ 35 ]. Several VR educational applications have been designed for STEM (Science, Technology, Engineering, Mathematics) domains [ 9 , 45 , 59 ], as interaction with such environments has shown, among other things, gains in deep and certain conceptual understanding, experimental experience and problem-solving ability [ 23 ]. The exploratory character of the virtual worlds that offers free navigation using the first-person user viewpoint may be the reason why VR applications are educationally superior also to multimedia [ 66 ].…”
Section: Introductionmentioning
confidence: 99%